2017
DOI: 10.1074/jbc.m116.764076
|View full text |Cite
|
Sign up to set email alerts
|

Cystinosin, the small GTPase Rab11, and the Rab7 effector RILP regulate intracellular trafficking of the chaperone-mediated autophagy receptor LAMP2A

Abstract: The lysosomal storage disease cystinosis, caused by cystinosin deficiency, is characterized by cell malfunction, tissue failure, and progressive renal injury despite cystine-depletion therapies. Cystinosis is associated with defects in chaperone-mediated autophagy (CMA), but the molecular mechanisms are incompletely understood. Here, we show CMA substrate accumulation in cystinotic kidney proximal tubule cells. We also found mislocalization of the CMA lysosomal receptor LAMP2A and impaired substrate translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 52 publications
6
90
1
Order By: Relevance
“…Our finding that RILP over-expression had no beneficial effect on autophago-lysosomal aggregate clearance was unexpected given the important role of RILP for lysosomal degradation of other substrates, including EGF receptor and LDL (Cantalupo et al 2001) and its involvement in chaperone-mediated autophagy (Zhang et al 2017). Yet, RILPdependent EGF receptor degradation was supported by Rab7 mutants associated with Charcot-Marie-Tooth (CMT) neuropathy (Spinosa et al 2008), whereas we previously Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our finding that RILP over-expression had no beneficial effect on autophago-lysosomal aggregate clearance was unexpected given the important role of RILP for lysosomal degradation of other substrates, including EGF receptor and LDL (Cantalupo et al 2001) and its involvement in chaperone-mediated autophagy (Zhang et al 2017). Yet, RILPdependent EGF receptor degradation was supported by Rab7 mutants associated with Charcot-Marie-Tooth (CMT) neuropathy (Spinosa et al 2008), whereas we previously Fig.…”
Section: Discussionmentioning
confidence: 73%
“…) and its involvement in chaperone‐mediated autophagy (Zhang et al . ). Yet, RILP‐dependent EGF receptor degradation was supported by Rab7 mutants associated with Charcot–Marie–Tooth (CMT) neuropathy (Spinosa et al .…”
Section: Discussionmentioning
confidence: 97%
“…Upon CMA activation, LAMP2A is actively excluded from these microdomains (60). Recent studies have shown that defective targeting of LAMP2A from Golgi to lysosomes is behind the low efficiency of CMA in the lysosomal storage disease cystinosis (61,62). These findings highlight LAMP2A trafficking as a possible additional mechanism for regulation of CMA activity.…”
Section: Specific Lysosomes Dedicated To Cmamentioning
confidence: 84%
“…Another role of CTNS, in addition to its potential involvement in mTORC1 signalling, is the altered chaperone mediated autophagy, as shown by two studies from Napolitano et al [37] and Zhang et al [36]. They observed impaired chaperone mediated autophagy (CMA) in cystinotic mouse skin fibroblasts presenting dislocation of LAMP2A (CMA receptor) and accumulation of GAPDH (CMA substrate).…”
Section: Functional Characteristics Of Ctns Mutationsmentioning
confidence: 90%
“…This was also true for CTNS-LKG, which is an alternative splice variant of CTNS, primarily targeted to the plasma membrane and other lysosomal/endosomal vesicles. Based on these results, it was suggested that CTNS is a necessary cofactor for LAMP2A trafficking [36,37].…”
Section: Functional Characteristics Of Ctns Mutationsmentioning
confidence: 99%